2018
DOI: 10.1073/pnas.1810379115
|View full text |Cite
|
Sign up to set email alerts
|

A unique ferredoxin acts as a player in the low-iron response of photosynthetic organisms

Abstract: SignificanceIron limits the growth of photosynthetic organisms, especially in marine environments. Understanding the response of photosynthetic organisms to changing iron concentrations is therefore important for agriculture and biotechnology. We have identified a protein that is essential for the correct response to changing iron concentrations in photosynthetic bacteria (cyanobacteria). This protein was previously annotated as an electron transfer component of photosynthesis, called Fed2, and contains an iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 60 publications
0
30
0
Order By: Relevance
“…Fdx2 ( sll138 ) has an E m of −243 mV ( 28 ), similar to the E m of the Fld semiquinone. Notably, Fdx2 has a unique intracellular role compared with Fdx1 in mediating iron homeostasis and chlorophyll accumulation, and it is conserved in photosynthetic microbes ( 27 , 29 ).…”
Section: Resultsmentioning
confidence: 92%
“…Fdx2 ( sll138 ) has an E m of −243 mV ( 28 ), similar to the E m of the Fld semiquinone. Notably, Fdx2 has a unique intracellular role compared with Fdx1 in mediating iron homeostasis and chlorophyll accumulation, and it is conserved in photosynthetic microbes ( 27 , 29 ).…”
Section: Resultsmentioning
confidence: 92%
“…Fed2 from Syn. 6803, which was found to be involved in the response to changing environmental iron concentrations [13], as well as Fd3 from T. elongatus. All Fds from this branch contain a Cterminal extension (Supp.…”
Section: Phylogeny Of Cyanobacterial Fdsmentioning
confidence: 99%
“…The phylogenetic analysis of most cyanobacterial Fds revealed that residues Ser/Val of the to play a role in the response to low-level iron, possibly related to its specific C-terminal extension [13]. Unfortunately, no Fd from this group has been studied so far structurally, although one gene copy of such Fd is present in each cyanobacterial strain sequenced to date.…”
Section: Discrimination Of Fd2 Against Fnrmentioning
confidence: 99%
See 1 more Smart Citation
“…6F), thus excluding this possibility. Recently, a cyanobacterial ferredoxin, Fed2, was shown to play a role in iron sensing and regulation of the IsiA antenna protein, a protein which is typically expressed when cells are exposed to low-iron conditions (Schorsch et al 2018). Similar to Fed2, it is possible that CytM plays a regulatory role in the cell, rather than being directly involved in electron transport.…”
mentioning
confidence: 99%